INNOVACIÓN EN LA PLANIFICACIÓN CURRICULAR DE LAS CARRERAS DE LA EDUCACIÓN SUPERIOR - Moncayo Gallegos, Édgar (2024)
The ever-changing character of science and technology oblige us to redefine current educational models and curricular planification from its basis. lt is indispensable to reinforce the role of research as the fundamental transversal axis of the training provided by the university as a daily classroom activity, starting with undergraduate students and making it mandatory in graduate programs. The growing contradiction lies in between the needs of a labor market that supposedly offers secure employment to recent graduates and the imperatives of our country's socio-economic development. Curricular planning needs to be directly relatad to the constitutional principie regarding the "appropriateness" of higher education. The motto of strong correlation with society needs to be identified once again in the historical development of Academia so as to develop its learning and research activities within the surrounding society, in touch with real flesh and bone people that experience concrete problems and necessities in the short, medium and long run. Without a doubt society provides the best labs from which the most advanced research projects can emerge. On the other hand, university-society correlation, from the point of view of curricular planning has to be integrated in syllabi and learning results of every classroom. Learning results are formulations that specify the knowledge that the student will develop along with related capacities that should result from any particular classroom experience. The key points in curricular development are: Redefinition of the basis for the curricular design and construction. • Multiple articulations of leaming envlronments • Reconsider the role of professors New organization for research activities so as to produce scientific knowledge in the daily life of educational spaces. • Organizational change of IES (¡1), towards network and modular models • Professional training based on universal values • Promotion of linguistic and cultural diversity Defesne of academia freedom and plurality in the University • Promotion of generic learning results